Teachers’ Challenges in Virtual Learning Process to Maximize The Students’ Achievement in 4.0 Era at UPT SMPN 1 Duampanua - Mansyur, Desy; Nur, Rafi'ah; Larekeng, Siti Hajar (Pascasarjana Universitas Negeri Makassar, 2023)
This study is aimed to find out the teachers’ challenges in virtual learning process to maximize the achievement of High School students in Indonesia. This research applied qualitative descriptive research with 5 English teachers as subjects of this research. The instruments are used in this research were interview and observation. The data has been analyzed by three steps according to Miles and Huberman theory. The results of this research showed that (a) the teachers’ challenges in virtual learning process are students’ far distance from internet sources, (b) difficult to access the clear explanation from the teachers and students, (c) lack of motivation to teach in limit access of students’ distance and network trouble, and (d) students’ less knowledge if using the internet and difficult to start the meeting using a different application. This study reveals that many challenges come over when the teachers applied virtual learning. Most of teachers were getting into trouble when entering the class if the students did not attend in virtual class because of far distance from internet sources. Another difficulty that challenges the teacher is their lack of giving motivation was not ineffective to teach their class. And the limit of network access made the students in loading to respond to the teachers' explanation and assignment to evaluate their knowledge.